2012
DOI: 10.1038/cddis.2012.105
|View full text |Cite
|
Sign up to set email alerts
|

The P2X7 receptor is a key modulator of aerobic glycolysis

Abstract: Ability to adapt to conditions of limited nutrient supply requires a reorganization of the metabolic pathways to balance energy generation and production of biosynthetic intermediates. Several fast-growing cells overexpress the P2X7 receptor (P2X7R) for extracellular ATP. A feature of this receptor is to allow growth in the absence of serum. We show here that transfection of P2X7R allows proliferation of P2X7R-transfected HEK293 (HEK293-P2X7) cells not only in the absence of serum but also in low (4 mM) glucos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
127
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(139 citation statements)
references
References 46 publications
6
127
0
1
Order By: Relevance
“…Grol and coworkers showed that activation of P2X7 leads to a dramatic, glucose-dependent increase in metabolic acid production by osteoblasts [31]. In addition, work from another lab has shown that heterologous expression of P2X7 in vitro leads to upregulation of glycolytic enzymes and an increase in lactate production [32]. Thus, overall energy expenditure may be less in mice lacking functional P2X7 receptors, resulting in increased accumulation of fat as the animals age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Grol and coworkers showed that activation of P2X7 leads to a dramatic, glucose-dependent increase in metabolic acid production by osteoblasts [31]. In addition, work from another lab has shown that heterologous expression of P2X7 in vitro leads to upregulation of glycolytic enzymes and an increase in lactate production [32]. Thus, overall energy expenditure may be less in mice lacking functional P2X7 receptors, resulting in increased accumulation of fat as the animals age.…”
Section: Discussionmentioning
confidence: 99%
“…This P2X7-induced increase in proton efflux is dependent on the activity of phosphatidylinositol 3-kinase and the presence of glucose. It has also been shown that heterologous expression of P2X7 in HEK293 cells promotes aerobic glycolysis and increases levels of glycolytic enzymes and glycogen stores [32]. Therefore, P2X7 activation enhances cellular energy metabolism, suggesting a role for this receptor in energy homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“…A site of intersection between glycolysis and the inflammasomes might be the P2X7R. Very recently, we reported that cells expressing the P2X7R have a very active aerobic glycolysis and that agents known to stimulate aerobic glycolysis, such as mitochondrial uncouplers, require P2X7R expression (Amoroso et al, 2012). Interestingly, cells expressing the P2X7R overexpress key glycolytic enzymes such as glyceraldehyde 3-dehydrogenase, pyruvate kinase M2, pyruvate dehydrogenase kinase, and phosphofructokinase, as well as the transcription factor hypoxia inducible factor (HIF)-1a.…”
Section: Nlrp3mentioning
confidence: 99%
“…5 Extracellular ATP is the natural ligand of P2Y metabotropic and P2X inotropic receptors, among which P2X7 is the best candidate responsible for cancerassociated ATP effects, as it has shown an intriguing ability to confer a growth advantage to cancer cells in in vivo models. 1 The growth-promoting activity of P2X7 may be related to the proliferative advantage conferred to tumor cells under limiting growth conditions, such as serum and glucose deprivation, [6][7][8] to the stimulation of vascular endothelial growth factor (VEGF) secretion and to the facilitation of extracellular matrix invasion. 1,2,9 Although P2X7 expression and activity has been reported in several cancers 10,11 the tumor-promoting pathways activated by P2X7 are largely unknown.…”
Section: Introductionmentioning
confidence: 99%